Estabilização da tutela provisória de urgência antecipada requerida em caráter antecedente - Scarpelli, Natália Cançado (2016)
The scope of this dissertation is to analyze, through a vast bibliographic research, the interlocutory advance injunction (also called interlocutory relief) stabilization technique recently incorporated in our legal system with the edition of the 2015 Civil Litigation Code. In regards to its structure, this work is divided in five chapters. The first chapter discusses the historical evolution of the interlocutory injunction focusing in the characterization of said institute by Italian doctrine, as well as its development in the Brazilian environment analyzing the precautionary injunction introduced in our legal system with the 1939 Civil Litigation Code and the preliminary injunction introduced with the 1973 Civil Litigation Code. The second chapter presents the treatment dispensed to the interlocutory injunction by foreign legal systems, specifically Italian, German, French and Portuguese Law. The third chapter assesses Brazilian current rules related with the interlocutory injunction through examination of the applicable provisions in the 2015 Civil Litigation Code. The fourth chapter specifically analyzes the procedures involved in filing motions for interlocutory injunctions of urgent and advance natures. At last, the fifth chapter is dedicated to a thorough exam of all specifics and potential issues related with the interlocutory advance injunction stabilization technique. The objective of this work is, supported in solid doctrine, to bring solutions to questions and doubts derived from the interpretation of Article 304 of the 2015 Civil Litigation Code in its concise terms. The ultimate goal is to achieve the dynamic construction of the entire procedure required to stabilize the interlocutory advance injunction and allow the practical application of such technique to ensure that Brazilian Litigation systems may take advantage of this application